2014
DOI: 10.1590/0101-60830000000007
|View full text |Cite
|
Sign up to set email alerts
|

Lisdexamfetamine dimesylate in the treatment of attention-deficit/hyperactivity disorder: pharmacokinetics, efficacy and safety in children and adolescents

Abstract: Background: Psychostimulants (methylphenidate and amphetamines) are considered first-line therapy for attention-deficit/hyperactivity disorder (ADHD). Lisdexamfetamine dimesylate (LDX) is a new psychostimulant approved for the treatment of ADHD in Brazil. The pharmacologically active fraction, d-amphetamine, is gradually released by hydrolysis of the LDX prodrug. Objectives: To perform a systematic review of the literature of the efficacy and safety of LDX in the treatment of ADHD in children and adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 56 publications
1
0
0
1
Order By: Relevance
“…The sample used in this study was small, and the multifaceted nature of the findings indicated that the study’s conclusions needed to be interpreted with caution and that more studies are needed on the influence of LDX on sleep in larger samples of children with ADHD. 20 Thus, these findings were convergent with those of Mattos, 27 where its effectiveness was evidenced and adverse effects, when present, were considered mild to moderate.…”
Section: Discussionsupporting
confidence: 66%
“…The sample used in this study was small, and the multifaceted nature of the findings indicated that the study’s conclusions needed to be interpreted with caution and that more studies are needed on the influence of LDX on sleep in larger samples of children with ADHD. 20 Thus, these findings were convergent with those of Mattos, 27 where its effectiveness was evidenced and adverse effects, when present, were considered mild to moderate.…”
Section: Discussionsupporting
confidence: 66%
“…Há também o uso de outras substâncias neuroestimulantes, como a classe das anfetaminas que possui representantes como o metilfenidato, mais comumente conhecido como ritalina, e a lisdexanfetamina, cujo nome comercial é venvanse. Esta droga, por ser um pró-fármaco inativo, necessita de ser metabolizada para a sua forma ativa (d-anfetamina) por meio da hidrolise, possuindo um efeito mais prolongado a partir de uma única dose diária (MATTOS, P., 2014). Esses fármacos estimulam diversas áreas do sistema nervoso central, ativando o córtex e aumentando o nível de vigília, apesar de seus efeitos ainda estarem sendo observados.…”
Section: M 2017)unclassified